Peningkatan Kemampuan Menulis Teks Argumentatif Yang Koheren Padatulisan Mahasiswastiba Saraswati Denpasar - Santang, Santang (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 24 No 1 (2017): Maret, 2017)
The ability of writing coherence text is one of the important material in writing competence of university level. In reality, there are some lack of skill in writing text of university students. Therefore, this research is implemented to improve university level students’ coherence in text through the learning of coherence. The implementation of this classroom action research aims to answer the problems that have been formulated that are: (1) How are the scores of the students obtained in cycle 1? (2) How are the scores of the students obtained in the last cycle? (3) How is the argumentative text coherence by the students after the implementation of coherence learning? Therefore, the aim of this research is to: (1) explain the score results that the students obtained in cycle 1; (2) explain the score results that the students obtained in the last cycle; (3) explain the argumetntative text coherence by the students after the implementation of coherence learning.   For collecting the data, the researcher use qualitative and quatitative approach. The data obtained from the students writing in form of qualitative. The results were analyzed based on the scoring rubric and assessed in the form of quantitative. Presentation of the results of the data analysis is presented descriptively.   The results showed coherence learning is proven to increase the ability to write an argumentative text of students of STIBA Saraswati Denpasar. The mean score obtained by students in cycle 1 was 63,1does not vary much with the results of the acquisition of students’ scores on pre-observation stage is 60,4. This shows there is no difference between the scores of students at the stage of pre-observation compared in cycle 1, which have not implemented the coherence learning. In cycle 2, the acquisition of students’ scores have improved is 77,2, which is when the learning text coherence implemented. In cycle 3, it can be seen an increasing on the acquisition of students’ scores is 85,7. Based on the acquisition of students’ scores above it can be stated that, instructional text coherence can improve students’ scores acquisition in writing competence.